Quality assurance in anatomic pathology: automated SNOMED coding. - Carter, K J (1996)
This case study details the set-up and implementation of the PathNet autocoder (Cerner Corporation) in a busy anatomic pathology laboratory. After initial start-up, procedures were developed to improve the system's performance. Four classes of software coding errors were identified, and an index was developed to measure the number of cases between errors (CBE). Through modifications in the program, the CBE increased sharply by the end of the six-month study period. During the last three months of the study, the efficiency of case retrieval was tested by comparing manual and electronic methods on the same reference cases. This demonstrated significant time saving and removed the variability of manual coding. The technique employed in this study may assist other institutions seeking to implement such a coding system within their respective environments.